Application of a spatial interaction model in Chiang Mai, Thailand - Prakin Arunotong; Fukuda, Atsushi; Yordphol Tanaboriboon; Mori, Hiroshi; The Government of Australia (Bangkok : Asian Institute of Technology, 1991)
In this study, a spatial interaction model was developed on the basis of the availability of data and socio-economic situation of the Chiang Mai urban area . In order to describe the interaction between land use and transportation , the urban system was divided into three major sectors, namely, a basic sector, a service sector, and a household sector. The basic sector is the export sector, in which employment and location are not affected by local events. The location and leveL of the remaining sectors are depended on the location and level of the basic sector. The model structure consists of the rural- urban migration concept and the Lawry's concept . Based on the Lawry's concept the model structure can sub-divided into two major allocation submodels, namely, the residential location submodel and the service location submodel. In this study, urban activity groups were allocated through the study area according to their travelling behaviours, and were constrained by the buildings and the transportation network . For calibration and prediction steps, the model was calibrated by adjusting its parameters so as to produce as closely as possible existing urban activities. Then, the model was applied to study the number of policy issues relevant to fast- growing of the Chiang Mai urban area. These policies included new transportation facilities, increased labour- force participation , and changes in land- use patterns. Finally, the model outputs indicated that basic employment, service employment, and population seemed to di versify from inner areas to outer areas when urban development policies were implemented.
A Thesis Submitted in Partial Fulfillment of the Requirements for the Degree in Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1991
Keywords: Urban transportation -- Thailand -- Chiang Mai; Land use, Urban -- Thailand -- Chiang Mai